An unusual presentation of blast phase in JAK 2 mutated polycythemia vera - Latha Abraham; Mobin Paul (Elsevier, 2021)
Leukemic transformation in Polycythemia Vera (PV) is described as a rare and late event, less common than primary myelofibrosis (PMF). Blast phase in PV (PV-BP) develops at a median time of 12.8 years from diagnosis which implies a long-lasting exposure to myelosuppressive agents. Acute megakaryocytic leukemia (FAB M7) and acute myelomonocytic leukemia (FAB M4) are the common morphologic types described in blast phase of myeloproliferative neoplasms (MPN). Here we report a case of a 61 year old male who progressed to blast phase within three years of diagnosis of PV and was on cytoreduction with hydroxyurea. The leukemic transformation occurred in the form of pure erythroid leukemia (FAB M6) and was not preceded by a phase of documented post PV myelofibrosis (post PV- MF). The unusual features in this case include the short period from initial diagnosis to leukemic transformation and the uncommon morphologic subtype.